Digital Marketing Training to Increase Luwuk Farmers' Association Sales - Irwan Moridu; Wahyudin Rahman; Adrian Polim; Fitri Devi Lestari Izaak; Arisanjaya Doloan (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
The goal of this PKM is to solve partner issues through digital sales applications (digital marketing) so that PPL products can reach a wide number of people. via a participatory approach, activities for farmers are being implemented by working together to develop answers via digital sales methods. Indonesia, like the rest of the world, is going through difficult circumstances. This is because the COVID-19 pandemic continues to spread, causing people's income to fall. As a result, one must be able to comprehend the numerous benefits and roles of using digital tools, motivating citizens and entrepreneurs to use digital tools in all activities. The advancement of digital marketing has an impact on the advancement of product advertising. The strategy employed to attain this goal is discussion combined with direct training at the Luwuk Farmers Association. By always following health rules, keeping your distance, and wearing a mask, this method is deemed in conformity with the goal of this service. It is intended that by participating in this activity, people would gain a better understanding of what it means to use digital marketing to boost corporate competitiveness. The majority of members feel optimistic about carrying out this activity.